G. Evelyn Hutchinson and the invention of modern ecology - Slack, Nancy G. (Yale University Press, 2010)
"Stephen J. Gould declared G. Evelyn Hutchinson the most important ecologist of the twentieth century. E.O. Wilson pronounced him "one of the few scientists who could unabashedly be called a genius." In this fascinating book, Nancy G. Slack presents for the first time the full life story of this brilliant scientist who was also a master teacher, a polymath with interests ranging from medieval art to the dangers of eutrophication, and a delightful friend and correspondent" "Slack enjoyed full access to Hutchinson's archives and conducted extensive interviews both with Hutchinson himself and with his students, colleagues, and friends. She evaluates his contributions to theoretical ecology, limnology (the study of fresh-water ecosystems), biogeochemistry, population ecology, and the creation of the new fields of systems ecology and radiation ecology, and she discusses his profound influence as a mentor. The book also looks into his personal life, which included three very different wives, a refugee baby under his care during World War II, friendships with such contemporaries as Rebecca West, Margaret Mead, and Gregory Bateson, and a host of colleagues and friends on four continents. Filled with information available nowhere else, this book draws a vibrant portrait of a giant in the discipline of twentieth-century ecology who was also a man of remarkable personal appeal."--Jacket.